Legal Protection For Victims Of Fraud In Buying And Selling Through Social Media According To Law Number 8 Of 1999 Concerning Consumer Protection And Law Number 19 Of 2016 Concerning Information And Electronic Transactions - Hariyanto; Hasdiana Juwita Bintang (International Journal of Society and Law, 2024)
The rapid development of e-commerce has transformed buying and selling activities into a seamless online process, offering convenience for both sellers and buyers. However, this shift has also increased the risk of fraud in online transactions, particularly through social media platforms such as Instagram, Facebook, and Twitter. Common issues include non-delivery of goods, receipt of defective or incorrect items, and fraudulent schemes exploiting buyers' trust. This study examines the legal framework governing fraud in online transactions in Indonesia, focusing on Law Number 8 of 1999 concerning Consumer Protection and Law Number 19 of 2016 concerning Information and Electronic Transactions. It explores the challenges in law enforcement and evaluates the legal protections available for victims of online fraud. The findings highlight gaps in legal implementation and suggest measures to enhance the effectiveness of legal protection for consumers in the digital marketplace.